Prevalence and care-seeking for chronic diseases among Syrian refugees in Jordan. (December 2015) - Doocy, Shannon; Lyles, Emily; Roberton, Timothy; Akhu-Zaheya, Laila; Oweis, Arwa; Burnham, Gilbert
Abstract Background There are currently more people displaced by conflict than at any time since World War II. The profile of displaced populations has evolved with displacement increasingly occurring in urban and middle-income settings. Consequently, an epidemiological shift away from communicable diseases that have historically characterized refugee populations has occurred. The high prevalence of non-communicable diseases (NCDs) poses a challenge to in terms of provision of appropriate secondary and tertiary services, continuity of care, access to medications, and costs. In light of the increasing burden of NCDs faced by refugees, we undertook this study to characterize the prevalence of NCDs and better understand issues related to care-seeking for NCDs among Syrian refugees in non-camp settings in Jordan. Methods A cross-sectional survey of 1550 refugees was conducted using a multi-stage cluster design with probability proportional to size sampling to obtain a nationally representative sample of Syrian refugees outside of camps. To obtain information on chronic conditions, respondents were asked a series of questions about hypertension, cardiovascular disease, diabetes, chronic respiratory disease, and arthritis. Differences by care-seeking for these conditions were examined using chi-square andt -test methods and characteristics of interest were included in the adjusted logistic regression model. Results Among adults, hypertension prevalence was the highest (9.7 %, CI: 8.8–10.6), followed by arthritis (6.8 %, CI: 5.9–7.6), diabetes (5.3 %, CI: 4.6–6.0), chronic respiratory diseases (3.1 %, CI: 2.4–3.8), and cardiovascular disease (3.7 %, CI: 3.2, 4.3). Of the 1363 NCD cases, 84.7 % (CI: 81.6–87.3) received care in Jordan; of the five NCDs assessed, arthritis cases had the lowest rates of care seeking at 65 %, (CI:0–88, p = 0.005). Individuals from households in which the head completed post-secondary and primary education, respectively, had 89 % (CI: 22–98) and 88 % (CI: 13–98) lower odds of seeking care than those with no education (p = 0.028 andp = 0.037, respectively). Refugees in North Jordan were most likely to seek care for their condition; refugees in Central Jordan had 68 % (CI: 1–90) lower odds of care-seeking than those in the North (p = 0.047). Conclusion More than half of Syrian refugee households in Jordan reported a member with a NCD. A significant minority did not receive care, citing cost as the primary barrier. As funding limitations persist, identifying the means to maintain and improve access to NCD care for Syrian refugees in Jordan is essential.